Microsatellite stable metastatic colorectal cancer without liver metastasis may be preferred population for regorafenib or fruquintinib plus sintilimab as third-line or above therapy:A real-world study - Nie, Caiyun; Lv, Huifang; Chen, Beibei; Xu, Weifeng; Wang, Jianzheng; Liu, Yingjun; Wang, Saiqi; Zhao, Jing; He, Yunduan; Chen, Xiaobing (Frontiers in Oncology, 2022)
Objectives: The antitumor activity of nivolumab plus regorafenib in colorectal cancer from a phase Ib REGONIVO study is encouraging. The present study was conducted to evaluate the efficacy and safety of regorafenib or fruquintinib plus sintilimab as third-line or above therapy in patients with microsatellite stable(MSS) metastatic colorectal cancer. Methods: Patients with MSS metastatic colorectal cancer who have failed from prior treatment and received regorafenib or fruquintinib plus sintilimab as third-line or above therapy from January 2019 to December 2020 were prospectively analyzed based on real-world clinical practice. The primary end point was progression free survival (PFS). Secondary end points included objective response rate (ORR), disease control rate (DCR), overall survival (OS),and safety. Results: 42 patients received regorafenib plus sintilimab(RS), and the other 30 patients received fruquintinib plus sintilimab(FS). In the general population, the ORR and DCR were 13.9% and 70.8%, and the median PFS and OS was 4.2(95% CI=2.9-5.5) and 10.5 (95% CI=8.6-12.4) months, respectively. There were no statistically significant differences between RS and FS group in PFS (3.5(2.2-4.8) vs. 5.5(3.5-7.5) months, P=0.434) and OS (11.0(7.0-15.0) vs. 10.5(3.8-17.2) months, P=0.486). Subgroup analysis suggested that patients without liver metastasis responded well to this combination regimen(ORR: 21.4% vs. 9.1%) and obtained better OS(26(8.8-43.2) vs. 10.0(7.4-12.6) months, P=0.016). The incidence of Grade 3-4 adverse events(AEs) was 15.3% and the toxicities were generally tolerable and manageable. Conclusions: Regorafenib or fruquintinib plus sintilimab as third-line or above therapy provide a feasible treatment regimen for MSS metastatic colorectal cancer with tolerated toxicity. Patients without liver metastasis may be the preferred population for this combination regimen.